Towards Sentiment Analysis in Agile Development Environments - Gramajo, María Guadalupe (2019)
In agile software development projects, user stories are written in natural language in order to describe the functionalities and features requested by interested parties. Given the ambiguous nature of natural language, user stories may reflect feelings intrinsically expressed by the product owner during requirements education tasks. While their visualization and identification are complex, word processing and sentiment analysis techniques can be applied to extract useful and valuable information for the development team. For that reason, this paper proposes a methodology to analyze the affective dimension of user stories, considering the feelings and emotions that affect the communication process amongteam members and identify how these factors impact the software development process, specifically in activities related to the definition and specification of requirements.